The SIRT6-Autophagy-Warburg Effect Axis in Papillary Thyroid Cancer - Yang, Zhou; Huang, Renghong; Yu, Weiping; Min, Zhijun; Ye, Min (Frontiers in Oncology, 2020)
In our previous study, we have demonstrated SIRT6 promotes aggression and epithelial-mesenchymal transition (EMT) in papillary thyroid cancer (PTC). In this study, we focused on the regulatory axis between SIRT6-Autophagy-Warburg effect. We innovatively confirmed overexpression of SIRT6 depleted histone H3 lysine 56 acetylation (H3K56ac) of NRROS in vitro, thus increased reactive oxygen species (ROS). Then, accumulated ROS activated endoplasmic reticulum stress (ER-stress), and subsequently induced autophagy. Furthermore, the overexpression of SIRT6 inhibited Glucose Transporter 1 (Glut1) via autophagic degradation, thus ulteriorly suppressed Warburg effect. Treatment of ROS scavenger N-acetyl-L-cysteine (NAC, 5mM) or autophagy inhibitor chloroquine (CQ) both rescued the inhibition of Warburg effect. In addition, higher concentration of NAC (15mM) deepened the inhibited Warburg effect. This concentration-dependent bilateral effects of NAC in this process had been confirmed owe to regulation of AMPK signaling pathway. Finally, we further determined above mechanism in vivo via subcutaneous xenografts in nude mice applied with 18F-FDG PET/CT. In conclusion, we identified a SIRT6-ROS-ERstress-Autophagy-Glut1-Warburg effect axis in PTC, which may provide new target for therapy. In addition, NAC (low concentration) and CQ which previously been considered as tumor inhibitors, have been shown to promote tumorigenesis in PTC with high SIRT6 expression via activation of Warburg effect.